Knowledge, attitudes and practices concerning pertussis maternal immunization in a sample of Italian gynaecologists - Sara Mazzilli; Lara Tavoschi; Pier Luigi Lopalco (Taylor & Francis Group, 2021)
Infants are at risk of developing serious diseases as a consequence of pertussis infection. Thus, to protect newborns, many countries, including Italy, have introduced pertussis maternal immunization. However, despite the compelling evidence supporting Tdap vaccinations, the rates of coverage among Italian pregnant women have remained consistently very low. Numerous studies have shown that healthcare providers' recommendations are critical for achieving high maternal vaccination coverages. This study explores Italian gynecologists' knowledge, attitude and practices concerning pertussis maternal immunization. Between July 2018 and September 2018, we performed a national cross-sectional survey administered by e-mail using the mailing list of the Association of Italian Hospital Obstetricians and Gynecologists (AOGOI): the mailing list included more than 3500 members. A total of 451 respondents distributed throughout Italy completed the online survey. Overall, 275 (60.97%) respondents did not routinely recommend pertussis vaccination to pregnant women, mainly for suboptimal knowledge of the maternal pertussis vaccine, protocols, and guidelines: furthermore, 15.44% (69/447) of gynecologists were not aware of the pertussis vaccination program for pregnant women. Gynecologists working in the South or in the Islands of Italy were less aware about the need of administering Tdap in expectant mothers, suggesting that there is a potential risk of health inequalities based on differing levels of vaccine knowledge and recommendations across Italy. In order to enable healthcare professionals to provide accurate and timely information on pertussis immunization to pregnant women, targeted educational programs to improve gynecologists' knowledge on pertussis vaccination are needed.